Development of Interactive Learning Media: Context-Based E-Book APK and E-LKPD LiveWorksheets to Improve Students Mathematical Literacy - Imam Taukhit; Nasution, Nur Baiti (Pena: Jurnal Ilmu Pengetahuan dan Teknologi, 2025)
The lack of interactive learning media integrating digital technology and contextual models contributes to low mathematical literacy in Indonesia. This study aims to develop interactive media in the form of an Android-based E-Book (APK) and Electronic Student Worksheets (E-LKPD) via Live Worksheets using a contextual approach. Following the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), research was conducted with tenth-grade students at MA Ma'arif Walisongo Kedungwuni. Data were gathered using validation sheets for 8 experts (3 lecturers, 5 teachers) and student questionnaires, then analyzed quantitatively. Results indicate the media is "highly valid" with an average validation score of 4.3. Implementation results showed high practicality, achieving a student response score of 4.3 (very practical). The media effectively engages students in learning arithmetic sequences through real-world contexts. This research contributes to providing contextual digital learning tools that support the Merdeka Curriculum implementation